Pengaruh Ketersediaan Ruang Terbuka Hijau Terhadap Tingkat Kebisingan di Perumahan Sepanjang Jalan Lokal Primer, Kota Makassar - Sri Hasnianti Rahman; Shirly Wunas; Wiwik Wahidah Osman (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2020)
Noise due to traffic is one of the environmental pollution that commonly occurs in urban areas. One of the cases of noise pollution due to traffic occurs in housing located along Jalan Sunu, which is the primary local road in Makassar City. This road is the main access to the Ir. Sutami from the south of Makassar City. This study aims to determine the extent to which the current noise level is from the permitted quality standards, as well as to analyze the effect of the current availability of green open space on noise levels and to describe the role of green open space planning in reducing noise levels. This research was conducted from October 2019 to March 2020. Data were obtained from literature reviews and field observations. The analysis was carried out by calculating the equivalent noise level and statistical influence factor analysis in the form of multiple linear regression tests. The results showed that the current noise level, which is between 61.29 to 71.74 dB (A), has exceeded the quality standard for residential areas, namely 55 dB (A). The results of the multiple linear regression test show that the wider the green open space in the house yard and on the green lane of the road, the lower the exposure to traffic noise into the dwelling. The concept of green open space arrangement in reducing noise levels that can be applied, including placing vines and lush shrubs along the residential fence, planting vegetation at least 25%, ideally 75%, border areas and green lines, increasing the land cover ratio in the form of shrubs / shrubs, trees, and other types of vegetation that have a height and leaf cover that have the potential to be an optimal noise barrier.